2019
DOI: 10.1177/1054773818823334
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis Screening: Combining Early Warning Scores and SIRS Criteria

Abstract: Providing effective screening tools to nurses is necessary to improve patient outcomes and health care quality. This research examines if the modification of two electronic health record sepsis screening tools using a combined systemic inflammatory response syndrome (SIRS), modified early warning score (MEWS), and national early warning score (NEWS) criteria improves the recognition of sepsis by nurses. Medical-surgical/telemetry units at a medical center in the Midwest were examined using a quasiexperimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Considering the rapid progression from organ dysfunction A In-hospital mortality among those with suspected sepsis B ED-to-ICU admission among those with suspected sepsis C In-hospital mortality among those with an EHR-based sepsis diagnosis D ED-to-ICU admission among those with an EHR-based sepsis diagnosis to death in sepsis patients, as well as the difficulty establishing a sepsis diagnosis at triage, 23 providers must quickly identify patients at increased risk of poor outcomes when they present to the ED. Sepsis alerts often are built using SIRS criteria, 27 including the one used for sepsis surveillance at UCSF since 2012, 22 but the white blood cell count criterion is subject to a laboratory lag and could lead to a delay in identification. Implementation of a point-of-care bedside score alert that uses readily available clinical data could allow providers to identify patients at greatest risk of poor outcomes immediately at ED presentation and triage, which motivated us to explore the predictive performance of qSOFA, the Shock Index, and NEWS2.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the rapid progression from organ dysfunction A In-hospital mortality among those with suspected sepsis B ED-to-ICU admission among those with suspected sepsis C In-hospital mortality among those with an EHR-based sepsis diagnosis D ED-to-ICU admission among those with an EHR-based sepsis diagnosis to death in sepsis patients, as well as the difficulty establishing a sepsis diagnosis at triage, 23 providers must quickly identify patients at increased risk of poor outcomes when they present to the ED. Sepsis alerts often are built using SIRS criteria, 27 including the one used for sepsis surveillance at UCSF since 2012, 22 but the white blood cell count criterion is subject to a laboratory lag and could lead to a delay in identification. Implementation of a point-of-care bedside score alert that uses readily available clinical data could allow providers to identify patients at greatest risk of poor outcomes immediately at ED presentation and triage, which motivated us to explore the predictive performance of qSOFA, the Shock Index, and NEWS2.…”
Section: Discussionmentioning
confidence: 99%
“…20 MEWS cutoff scores of deterioration that trigger an evaluation vary within the literature based on patient population and clinical settings. 10,21,22…”
Section: Mews Guidementioning
confidence: 99%
“…Various clinical decision support tools (CDSTs) and existing early warning tools are used for the early identification of sepsis 9-12. Despite the availability of CDSTs, initial signs and symptoms of sepsis can be challenging to recognize.…”
mentioning
confidence: 99%
“…Our results support a correlation between inflammatory biomarkers and the mEWS but highlight the easier implementation of the mEWS into clinical decision-making. Kangas et al [26] found that combining the systemic inflammatory response syndrome (SIRS) criteria with the mEWS resulted in correctly capturing three times more sepsis diagnoses while triggering 46% fewer falsepositive alerts. Often biomarkers are used for evaluation of sepsis prior to culture results or in settings without clear symptoms.…”
Section: Predictive Value Of the Mewsmentioning
confidence: 99%